Tumors of the Central Nervous System, Volume 14 Glioma, Meningioma, Neuroblastoma, and Spinal Tumors - Hayat, M.A (Tumors of the Central Nervous System,, 2015)
This fourteenth volume of the series provides comprehensive, current information on the diagnosis, therapy and prognosis of brain tumors and spinal tumors. For the readers' convenience, contributions are organized into three categories of Pineal Tumors, Pituitary Tumors, and Spinal Tumors. Readers will find discussion of various aspects of a number of tumor types, including angiocentric glioma, pilomyxoid astrocytoma, pituicytoma, pediatric low-grade gliomas, meningiomas and spinal cord tumors. Expert oncologists, neurosurgeons, physicians, research scientists and pathologists from around the world have contributed to this extensive publication. Their chapters highlight practical experience and provide exceptional insight into the nature of cancer. The authors cover topics ranging from the use of molecular criteria in diagnosis and targeting of medicine, through evidence-based approaches, to in-depth discussion of long-term follow-up after surgery. This handbook, as earlier volumes in the series, will appeal to professionals involved in the treatment of cancer, as well as to researchers. The series crosses subjects of diagnosis, drug development, therapy and its assessment and prognosis of tumors of the central nervous system, cancer recurrence and resistance to chemotherapy.